Calibration of the Radio Neutrino Observatory in Greenland (RNO-G) - Welling, Christoph; Aguilar, Juan A.; Allison, Patrick; Besson, Dave; Bishop, Abigail; Botner, Olga; Bouma, Sjoerd; Buitink, S.; Castiglioni, W.; Cataldo, Maddalena; Clark, B. A.; Coleman, A.; et al. (Proceedings of 38th International Cosmic Ray Conference — PoS(ICRC2023), 2024)
The Radio Neutrino Observatory Greenland (RNO-G) is a radio detector for neutrinos with energies above ∼10 PeV. It is currently under construction at Summit Station, Greenland, with 7 out of 35 stations deployed so far. By measuring the radio pulses that are emitted when ultrahigh energy neutrinos interact in ice, each station can detect neutrinos over distances of several kilometer and functions as an independent detector. A station consists of a total of 24 antennas, which are divided into a shallow component of 9 logarithmic-periodic dipole antennas near the surface, and a deep component of dipole and slot antennas inside boreholes down to 100m depth. We present an overview of the calibration efforts for RNO-G and show first results of ice property studies, which are crucial for the RNO-G station calibration.
CRIS-Team Scopus Importer:2025-02-04